Characterisation of Phytophthora capsici, Causal Agent of Phytophthora Foot Rot Disease of Piper nigrum L. in Sarawak, Malaysia - Kavitha, Vinjeandran; Tu Anh, Vu Thanh; Kueh, Kiong Hook; Awang Ahmad Sallehin, Awang Husaini; Harry, Entebang; Freddy Yeo, Kuok San (Taylor & Francis Group, 2024)
Phytophthora capsici causes Phytophthora foot rot disease on Piper nigrum. The pathogen lacks comprehensive study in Sarawak, Malaysia. In this study, P. capsici was isolated and characterised morphologically and molecularly from ten farms across three divisions in Sarawak. The pathogenicity of the isolates was confirmed, and distinct colony growth patterns, sporangia morphologies, and radial growth rates were observed across different media. Torulose hyphae structures were consistently observed, and compatible mating types were present. Fifty-two isolates retrieved from this study were genotyped using five Inter Simple Sequence Repeats and three Random Amplified Microsatellites primers. The UPGMA tree showed a close relationship between populations. A higher diversity within populations (73%) than among populations (27%) was observed. This study provides the first baseline data on the diversity of P. capsici in Sarawak, offering insights for managing the disease’s impact on pepper cultivation and the potential risk of increasing genetic diversity.